2023
DOI: 10.1002/smll.202205412
|View full text |Cite
|
Sign up to set email alerts
|

Sol‐Gel‐Derived Ordered Mesoporous High Entropy Spinel Ferrites and Assessment of Their Photoelectrochemical and Electrocatalytic Water Splitting Performance

Abstract: The novel material class of high entropy oxides with their unique and unexpected physicochemical properties is a candidate for energy applications. Herein, it is reported for the first time about the physico‐ and (photo‐) electrochemical properties of ordered mesoporous (CoNiCuZnMg)Fe2O4 thin films synthesized by a soft‐templating and dip‐coating approach. The A‐site high entropy ferrites (HEF) are composed of periodically ordered mesopores building a highly accessible inorganic nanoarchitecture with large spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 126 publications
1
24
0
Order By: Relevance
“…23,24 They also have high proton conductivity, high chemical stability, abundant storage, and cost-effectiveness that are required for photovoltaic cells, photocatalytic water splitting, light-driven carbon dioxide reduction, and photocatalytic degradation of pollutants. 25–27…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 They also have high proton conductivity, high chemical stability, abundant storage, and cost-effectiveness that are required for photovoltaic cells, photocatalytic water splitting, light-driven carbon dioxide reduction, and photocatalytic degradation of pollutants. 25–27…”
Section: Introductionmentioning
confidence: 99%
“…23,24 They also have high proton conductivity, high chemical stability, abundant storage, and cost-effectiveness that are required for photovoltaic cells, photocatalytic water splitting, light-driven carbon dioxide reduction, and photocatalytic degradation of pollutants. [25][26][27] Bi 2 O 3 , a post-transition metal oxide with a gap of 2.8 eV and readily accessible two-electron redox couples has received increasing attention in recent years as the ideal alternative for large-scale applications and photocatalytic redox processes such as H 2 generation and CO 2 reduction, as well as many other interesting applications such as the degradation of organic pollutants, gas sensing, solid oxide fuel cells, ceramic glass fabrication, and optical coating, owing to its low toxicity, low cost, and abundant polymorphism. Therefore, it is anticipated that this material may also drive the four-electron water oxidation process under alkaline conditions, resulting in dualactive OER/HER catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, there is only one study available in literature reporting on the PEC performance of KLEtemplated ferrites, which explores periodically ordered highentropy spinel photoanodes. [47] Furthermore, Laberty-Robert et al demonstrated for PIB-PEO templated ordered mesoporous WO 3 photoanodes that the PEC photoresponse of the mesostructured species was increased compared to dense WO 3 thin films. These data are supported by the work of Yagi et al in which the high PEC water oxidation performance of small-sized mesoporous WO 3 photoanodes was assigned to both the high Chemistry-A European Journal surface area (158 m 2 /g) which offered a large amount of catalytically active oxidation sites and the shorter carrier diffusion length which was provided by the 4-6 nm sized pore walls.…”
Section: Introductionmentioning
confidence: 99%
“…The precise evaluation of these parameters and their dependence on the surface morphology and degree of crystallinity is of great importance to understand the limiting factors of mesoporous materials applied as photoelectrodes for solar water splitting. Up to now, there is only one study available in literature reporting on the PEC performance of KLE‐templated ferrites, which explores periodically ordered high‐entropy spinel photoanodes [47] . Furthermore, Laberty‐Robert et al.…”
Section: Introductionmentioning
confidence: 99%
“…(3) The narrowed bandgap, owing to optimally mixing different 3d transition elements, enables these materials to separate electrons and holes with greater ease and absorb full-wavelength sunlight more efficiently. This is attributed to the multiple low-intensity d–d conversions of different transition metals, whereby the charge carriers are excited from t 2g to the corresponding e g level, ultimately enhancing the solar energy absorption ability. Comparing the effects of Cu, Mo, and Cr on narrowing the bandgap, we find that Cu and Mo exhibit a better effect compared to Cr. Consequently, the evaporation rates of AlNiCoFeCu-O x and AlNiCoFeMo-O x are higher than that of AlNiCoFeCr-O x .…”
mentioning
confidence: 99%